Penegakan Hukum Terhadap Penyebarluasan Foto Vulgar di Media Sosial Disertai Pemerasan dan Pengancaman di Kabupaten Wajo - Andi Bau Mallarangeng; Andi Wahyuddin Nur; Martono; Muhammad Syahbana (Legal Journal of Law, 2025)
This article discusses law enforcement against the dissemination of vulgar photos on social media accompanied by blackmail and threats in Wajo Regency. The approach method applied in this study is empirical sociological law. The data collection techniques used are interviews and document studies. The analysis technique used in this study is using the descriptive analysis method. The results of the study indicate several factors that cause the dissemination of vulgar photos on social media accompanied by blackmail and threats, namely (1) public awareness of the importance of maintaining digital privacy, (2) revenge motivation is often the main driver behind this action, (3) problems in personal relationships, such as or dissatisfaction, can also drive this kind of detrimental action, (4) financial or financially oriented reasons. Law enforcement against the dissemination of vulgar photos on social media accompanied by blackmail and threats faces major challenges in handling these cases, especially related to the collection and verification of digital evidence.